Pemberdayaan Masyarakat dalam Memanfaatkan Lahan Pekarangan Kosong Melalui Program Kebun Sehat di Desa Kedawung Wetan Pasuruan - Muh. Ahyar; Nihlatul Falasifah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Community empowerment in utilizing empty yard land through the Healthy Garden program is an initiative in Buntalan Hamlet, Kedawung Wetan Village, Grati, Pasuruan to increase food independence and welfare. The method used is Asset-Based Community Development (ABCD) approach. This program focuses on community empowerment through the management of local assets, especially yard land that is not optimally utilized. The goal is to transform the land into a productive garden that produces vegetables, fruits, and medicinal plants to support the nutritional needs and health of the community. This empowerment process involves various stages, starting from discovery (identifying assets), dream (dreaming about the future), design (designing programs), define (determining actions), and destiny (implementing actions). The result is the formation of a healthy garden that functions as an example for the wider community and improves farming skills and local resource management. This program has a positive impact in reducing stunting rates, increasing food independence, and creating a healthier and more independent community in a sustainable manner.